2007
DOI: 10.1097/01.ajp.0000210936.50816.49
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' Reassessment of Postoperative Pain After Analgesic Administration

Abstract: Despite the focus on meeting standards of care in the area of pain management, there was an extraordinary lack of patient reassessment by nurses after the administration of analgesics. Given the raised awareness internationally on assessment generally and a lack of evidence focused on reassessment after an intervention, this may explain why research is failing to identify shifts in pain severity scores and indeed patient pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 26 publications
(17 reference statements)
0
20
1
2
Order By: Relevance
“…The as needed basis morphine was used to analyze whether the iden fi ca on of a worsening pain scenario would lead the nursing team to a therapeu c adjustment, a feature that was eventually verifi ed. Such data diff er from those of a previous study, which observed a lack of reassessment by the nursing team a er the analgesic interven on (19) . The seda on degree was one of the previous prerequisite assessment parameters for the administra on of the supplementary morphine.…”
Section: Morphine Consump Oncontrasting
confidence: 95%
“…The as needed basis morphine was used to analyze whether the iden fi ca on of a worsening pain scenario would lead the nursing team to a therapeu c adjustment, a feature that was eventually verifi ed. Such data diff er from those of a previous study, which observed a lack of reassessment by the nursing team a er the analgesic interven on (19) . The seda on degree was one of the previous prerequisite assessment parameters for the administra on of the supplementary morphine.…”
Section: Morphine Consump Oncontrasting
confidence: 95%
“…Patients should be asked repeatedly about their pain intensity and whether they need analgesia. A study conducted among nurses revealed that, of all patient-centered activities related to pain, only 4% of activities included repeated assessment of pain intensity after providing an analgesic 24. It is often necessary to reassess pain shortly after administering analgesia and, if necessary, to adjust the dose or type of analgesia 25…”
Section: Discussionmentioning
confidence: 99%
“…Nurses' key role in inpatient pain management (Bucknall, Manias & Botti, 2007) can extend to responsibility for pain assessment, basic analgesic prescription, and titration of patient-controlled analgesia (National Health Service, 2015). Many of these responsibilities are covered by guidelines on best practice in assessment and treatment (McCafferty & Pasero, 1999).…”
Section: Introductionmentioning
confidence: 99%